The Effect of Leadership and Competence on Organizational Citizenship Behavior (OCB) Mediated by Job Satisfacti - Ningrum , Widya; Liana, Lie (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the effect of leadership and competence on Organizational Citizenship Behavior (OCB), mediated by job satisfaction. This research employs a quantitative approach with a population consisting of 58 employees of BPPKAD, Wonosobo Regency. The data were processed using SPSS version 26. The data analysis techniques include respondent description, variable description, validity test, reliability test, F-test, coefficient of determination (R²), t-test, and Sobel test. The results of the study indicate that leadership has a positive effect on job satisfaction, competence has a positive effect on job satisfaction, leadership has a positive effect on OCB, competence has a positive effect on OCB, and job satisfaction has a positive effect on OCB. However, job satisfaction does not mediate the effect of leadership on OCB, while job satisfaction mediates the effect of competence on OCB.